Den umulige hage: Rom og tid i hagemotivet i Livias villa - Olaussen, Hege (Nordlit, 2015)
The article discusses representations of time and space in the frescoes in the garden room of Empress Livia’s villa at Prima Porta, near Rome. The frescoes, dated to ca 30–20 B.C., decorates an underground chamber in a vast villa-complex and show an "impossible garden" in that its vegetation is simultaneously and continuously flowering, without any realistic connection to time. Through analysis of the vegetation’s spatial organization, the representation of birds and the chamber’s placement in the villa-complex, the article examines the significance of the garden, be it real or imaginary, as an arena for instilling and expressing Roman civic values and duties. It addresses the potential relevance of the villa’s imperial connection and questions whether the frescoes are to be read as expressions of "art of the state" or "state of the art".